Is single-inhaler triple therapy for COPD cost-effective in the UK? The IMPACT trial. Issue 1 (21st February 2022) - Martin, Alan; Shah, Dhvani; Ndirangu, Kerigo; Anley, Glenn A.; Okorogheye, Gabriel; Schroeder, Melanie; Risebrough, Nancy; Ismaila, Afisi S.
Background: The IMPACT trial demonstrated superior outcomes following 52 weeks of once-daily single-inhaler treatment with fluticasone furoate (FF)/umeclidinium (UMEC)/vilanterol (VI) (100/62.5/25 μg) compared with once-daily FF/VI (100/25 μg) or UMEC/VI (62.5/25 μg). This study evaluated the cost-effectiveness of FF/UMEC/VI compared with FF/VI or UMEC/VI for the treatment of chronic obstructive pulmonary disease (COPD) from a UK National Health Service perspective. Methods: Patient characteristics and treatment effects from IMPACT were populated into a hybrid decision tree/Markov economic model. Costs (GB£ inflated to 2018 equivalents) and health outcomes were modelled over a lifetime horizon, with a discount rate of 3.5% per annum applied to both. Sensitivity analyses were performed to test the robustness of key assumptions and input parameters. Results: Compared with FF/VI and UMEC/VI, FF/UMEC/VI provided an additional 0.296 and 0.145 life years (LYs) (discounted) and 0.275 and 0.118 quality-adjusted life years (QALYs), at an additional cost of £1129 and £760, respectively. Incremental cost-effectiveness ratios (ICERs) for FF/UMEC/VI were £4104/QALY and £3809/LY gained versus FF/VI and £6418/QALY and £5225/LY gained versus UMEC/VI. At a willingness-to-pay threshold of £20 000/QALY, the probability that FF/UMEC/VI was cost-effective was 96% versus FF/VI and 74% versus UMEC/VI. Results were similar in a subgroup of patients recommended triple therapy in the 2019 National Institute for Health and Care Excellence COPD guideline. Conclusions: FF/UMEC/VI single-inhaler triple therapy improved health outcomes and was a cost-effective option compared with FF/VI or UMEC/VI for patients with symptomatic COPD and a history of exacerbations in the UK at recognised cost-effectiveness threshold levels. This analysis demonstrates that fluticasone furoate (FF)/umeclidinium (UMEC)/vilanterol (VI) provides a cost-effective treatment option versus FF/VI or UMEC/VI for patients with symptomatic COPD in the UK https://bit.ly/3w7vQj9